Prognostics and health management : a practical approach to improving system reliability using conditioned-based data - Goodman, Douglas (Industrial engineer); Hofmeister, James P.; Szidarovszky, Ferenc (Wiley, 2019)
72 CHAPTER 2: APPROACHES FOR PROGNOSIS AND HEALTH MANAGEMENT (PHM) 1 2.1 Approaches for Prognosis and Health Management (PHM) 1 2.1.1 Model-based Prognostic Approaches 1 2.1.2 Data-driven Prognostic Approaches 2 2.1.3 Hybrid Prognostic Approaches 2 2.1.4 Objectives for this Chapter 3 2.1.5 Chapter Organization 3 2.2 Model-based Prognostics 2.2.1 Analytical Modeling 5 2.2.2 Distribution Modeling 10 2.2.3 Physics of Failure (PoF) and Reliability Modeling 12 2.2.4 Acceleration Factor (AF) 14 2.2.5 Complexity Related to Reliability Modeling 16 2.2.6 Failure Distribution 18 2.2.7 Multiple Modes of Failure: Failure Rate and FIT 19 2.2.8 Advantages and Disadvantages of Model-based Prognostics 19 2.3 Data-driven Prognostics 20 2.3.1 Statistical Methods 20 2.3.2 Machine Learning (ML): Classification and Clustering 26 2.4.